2023
DOI: 10.11591/ijphs.v12i2.22599
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth risk in mother with hypertensive disorders of pregnancy

Abstract: Preterm birth (PTB) is a major public health concern and is the leading cause of under-5 child mortality. Some studies suggest that hypertension disorders of pregnancy (HDP) play an important role in causing PTB. HDP is a term that includes chronic hypertension (CH), gestational hypertension (GH), and pre-eclampsia (PE). The association between the various types of HDP and PTB has not been studied specifically in prior research, yet. Therefore, the purpose of this study is to analyze risk differences among HDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…When examining gHTN and preterm birth, the association remained significant in both the crude and adjusted models. This aligns with the existing literature, which has established gHTN as a potential risk factor for preterm birth [16,17,40]. It should also be noted that although there is a stronger statistical association between gHTN and preterm birth compared to food desert exposure and preterm birth, this does not minimize the primary findings of our study and the negative impact inadequate food access has on birthing outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When examining gHTN and preterm birth, the association remained significant in both the crude and adjusted models. This aligns with the existing literature, which has established gHTN as a potential risk factor for preterm birth [16,17,40]. It should also be noted that although there is a stronger statistical association between gHTN and preterm birth compared to food desert exposure and preterm birth, this does not minimize the primary findings of our study and the negative impact inadequate food access has on birthing outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Studies suggest that HDP, such as gestational hypertension (gHTN), may be significant factors in the occurrence of preterm birth [16]. Arfandi et al (2023) reported that although preterm birth risk may differ by the type of HDP, each form of HDP carries a significant risk for preterm birth [17].…”
Section: Introductionmentioning
confidence: 99%